PENGARUH PENGAJARAN JARAK JAUH TERHADAP MOTIVASI BELAJAR TARUNA POLTEKIP TINGKAT III MANAJEMEN PEMASYARATAN A - Octha Octha (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Technological developments that occur at this time, especially in the field of education, are things that should be understood. Distance learning is an alternative way if you cannot carry out lectures directly in the classroom. Indirectly distance teaching can affect learning motivation. Learning motivation can emerge from the goal or drive to get the expected results. This research is to find out the effect of distance lectures on learning motivation of third-level polytechnic cadets in Penitentiary Management Class A as a research sample. The research method uses a type of quantitative research that explains and illustrates the effect of distance learning into an indicator of the success of learning motivation. Data analysis applies validity tests, formative tests, and simple linear regression. It can conclude that distance teaching influences the significant outcome of learning explanation of cadet polytechnic level III Corrections Management class A. The results of the data obtained indicate that there is a 76.2% significant influence on learning motivation. At the same time, the remaining 23.8% influenced by several other factors.